An experimental study on geometric accuracy in hybrid incremental sheet forming. Issue 4 (2nd October 2021) - Jagtap, Rahul; Kumar, Shailendra
ABSTRACT: In the present experimental study, influence of process parameters in hybrid incremental sheet forming (HISF) is studied. Stretch forming combined with ISF is used for forming of conical parts. Stretch forming or preforming is done in order to get the intermediate shape and thickness distribution. On the same setup final part shape is obtained using the conventional ISF process. A low cost hemispherical-ended wooden preforming tool is used for the preforming purpose. Tools used for ISF process are also hemispherical-ended in shape but having smaller diameters and are made up of stainless steel SS-305. Experiments are designed according to design of experiment (DOE) Taguchi method. Analysis of variance (ANOVA) is used to analyse the effect of process parameters namely preforming depth, tool diameter and pitch on response geometric accuracy. It is found that there is considerable effect of tool diameter on geometric accuracy of the formed part. Also, forming time is reduced considerably due to the preforming operation.